P575 Effect of etrasimod on immune cell subsets in colonic tissue of patients with ulcerative colitis: immunophenotyping analysis of colon biopsy samples from the phase 3 ELEVATE UC 52 and ELEVATE UC 12 trials. (30th January 2023) - Siegmund, B; Komori, H K; Abreu, M T; Vermeire, S; Dotan, I; Goetsch, M; Crosby, C; Ryan, R; Woolcott, J; Danese, S
Abstract: Background: Etrasimod is an investigational, once-daily, oral, selective sphingosine 1-phosphate receptor 1, 4, 5 (S1P1, 4, 5 ) modulator in development for the treatment of moderately to severely active ulcerative colitis (UC). Etrasimod reversibly sequesters specific lymphocyte subsets in lymph nodes, reducing circulating lymphocytes and resulting in fewer immune cells available to traffic to the gastrointestinal tract. To better understand how etrasimod reduces inflammation in UC, the phase 3 ELEVATE UC 52 and ELEVATE UC 12 trials included a per protocol exploratory immunophenotyping biomarker analysis in fixed-formalin paraffin-embedded (FFPE) colon biopsies. Methods: In ELEVATE UC 52 (NCT03945188) and ELEVATE UC 12 (NCT03996369), patients (16-80 years) with moderately to severely active UC were randomised 2:1 to once-daily etrasimod 2 mg or placebo (PBO). Characterization of immune cell types in colon biopsies were assessed at baseline, week 12, and week 52 (ELEVATE UC 52 only) by Epiontis ID, an epigenetic immune monitoring method. Biomarker levels for each lymphocyte subset were evaluated between responders vs nonresponders, defined by achievement of clinical efficacy criteria within each treatment group, using t -tests and nominal P values. Results: Colon biopsies were collected and analysed from 276 subjects in ELEVATE UC 52 (179 etrasimod, 97 PBO) and 150 subjects in ELEVATE UC 12 (97 etrasimod, 53 PBO). Etrasimod induced significant changes from baseline (nominal P value <0.05) in colonic T- and B-cell subsets at week 12 in ELEVATE UC 52 and ELEVATE UC 12 (Figure 1), which were maintained through week 52 in ELEVATE UC 52. At week 12, etrasimod induced significant reductions from baseline (nominal P value <0.05) in colonic T- and B-cell subsets expressing IL17A, FOXP3, CCR7, CXCR3, and LRP5A in responders vs nonresponders (Table 1). At week 12, etrasimod, but not PBO, induced significant reductions from baseline (nominal P value <0.05) in colonic CD8B-expressing T cells in responders vs nonresponders in ELEVATE UC 52; these trends were maintained through week 52. Significant effects on CXCR3, FOXP3, and LRP5A were observed in responders vs nonresponders in ELEVATE UC 12. Conclusion: In this per protocol exploratory analysis of two independent phase 3 trials, etrasimod induced changes from baseline in colonic tissue T- and B-cell subsets in subjects with UC, with nominally significant reductions observed in those who met response criteria. The reduction in activated immune cells in colonic tissue in responders suggests etrasimod induces a reduction in local inflammation that could contribute to remission. These findings are the first to report changes to immune cell subsets in colonic tissue in response to a S1P receptor modulator.